Combat and sacrifice: the culture of information crisis in teaching librarianship - Noone, Rebecca; Hicks, Alison (Information research, 2025)
Introduction. This paper extends recent research into the use of information crisis terminology within information studies to trace how the concept functions and is used within professional teaching librarian practice.  Method. Employing critical discourse analysis, the paper examines the conference proceedings from ten teaching librarian conferences (2014-2024), a database of information literacy lesson plans and the introductory chapters of selected practitioner-oriented handbooks to identify conventions of information crisis language within teaching librarianship.   Results. Findings suggest that teaching librarians’ discourse of information crisis is shaped through considerations of time and affect, which position educational work as both urgent and intense.  Conclusions. Concern that the use of evocative images and metaphors obscures teaching librarian labour as well as a reliance on a growing industry of information crisis solutions suggests the need for continued critical interrogation of the use of this term within librarianship.